PERANAN MEDIASI DALAM PENYELESAIAN SENGKETA BISNIS DI ERA DIGITAL - Delfina, Dinda (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The increasing complexity of business disputes that arise and the need for fast and effective resolution encourage further exploration of the role of mediation in the context of the digital era. Analysis of business disputes in the digital era is very important considering the rapid development of technology and its impact on the business world. The research method used is normative descriptive qualitative. Mediation has a significant role in resolving business disputes in the digital era. The advantages of mediation in terms of time and cost efficiency are a very valuable added value for the parties involved in business disputes. Clearer regulations are needed to accommodate technological developments and regulate competition in the digital era. Dispute resolution also needs to be supported by adequate legal infrastructure. Collaboration between government and business actors is key in dealing with business disputes in the digital era.